Studi Beban Pendinginan Ikan Menggunakan Brine Dengan Jenis Garam Berbeda - Rahmat Effendi Lubis; Ni Luh Yulianti; I Wayan Widia (Jurnal BETA (Biosistem dan Teknik Pertanian), 2020)
The purpose of this study was to determine the effect of using brine with different types of salt on cooling fish and its effect on cooling load, so that a combination of treatments that produced the lowest cold point and maximum ability were obtained to eliminate the total heat energy in fish. The raw materials used in this study are salts of NaCl, KCl, CaCl2 and tuna. The cooling process in this study uses ice and salt (brine) solutions with concentrations of each type of salt, namely 2%, 7%, and 12% of the weight of the cooling media. In this research, the first two stages were carried out, namely with air load, then continued with the hot load of fish for each cooling medium on different styrofoam boxes. From the results of this experiment, a decrease in the maximum cooling point of brine temperature of -2,46 °C was found in the treatment of NaCl salt concentration of 12% (a1b3), then brine solution which was able to keep the fish temperature at the lowest is -1.4 ° C from treatment a1b3 (NaCl salt) concentration of 12%.